Preference for Detail in Medical Illustrations Amongst Professionals and Laypersons. (June 2013) - Strong, Jesse; Erolin, Caroline
<x xml:space="preserve">Abstract</x> This study investigated the preferences of medical professionals and laypersons with respect to the level of detail shown in medical illustrations (i.e. graphic art shown in patient education materials) and the complexity of the subject being depicted (i.e. a visually simple versus a visually complex subject). Additionally, respondent's age, gender, and art background were recorded to yield further insight. The results showed that generally there was preference for high-detail (complex) illustrations between the two groups, though the professionals group was somewhat more diverse in their choices. The other variables had no impact on illustration preference.